2015
DOI: 10.3390/ijms161226185
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Expression of p63 in Mouse Epidermal Commitment

Abstract: The embryonic surface ectoderm is a simple flat epithelium consisting of cells that express the cytokeratins K8/K18. Before stratification, K5/K14 expression substitutes K8/K18 expression, marking the event called epidermal commitment. Previous studies show that the transcription factor p63 plays an essential role in epidermal commitment. However, detailed expression information of p63 during early epidermal development in mice is still unclear. We systematically studied the expression pattern of p63 in mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…These findings support a model in which p63 is essential for epidermal commitment, acting as a gatekeeper of the epithelial lineage (14). Consistent with this model, expression of p63 in mouse embryos is firstly induced in the surface ectoderm where Krt8 and Krt18 are expressed, and continuously increased during epidermal commitment (16). An alternative model is that p63 is not required for commitment towards the epidermal fate, as it was reported that a small number of Krt5 and Krt14 expressing cells was observed and that the morphology of cells and tissues was relatively normal in p63 knockout mice (5).…”
Section: Introductionsupporting
confidence: 85%
“…These findings support a model in which p63 is essential for epidermal commitment, acting as a gatekeeper of the epithelial lineage (14). Consistent with this model, expression of p63 in mouse embryos is firstly induced in the surface ectoderm where Krt8 and Krt18 are expressed, and continuously increased during epidermal commitment (16). An alternative model is that p63 is not required for commitment towards the epidermal fate, as it was reported that a small number of Krt5 and Krt14 expressing cells was observed and that the morphology of cells and tissues was relatively normal in p63 knockout mice (5).…”
Section: Introductionsupporting
confidence: 85%
“…Recently, spatio-temporal expression of p63 during normal mouse embryonic development was analyzed [ 26 ]. p63 expression was detected in ectodermal cells near the newly formed somites and the posterior part of the E8.5 embryo, preceding epidermal commitment.…”
Section: P63 Is Essential For Proper Epidermal Commitmentmentioning
confidence: 99%
“…As we have described in chapter 2, the simple epithelia-specific keratin pair, K8/K18, are expressed in keratinocyte progenitors, early on during embryonic skin development, and upon vertical epidermal stratification K8/K18 expression is then substituted by K5/K14, and becomes eventually lost in fully mature skin epidermis [9,10,74]. Overexpressing human K8 in mouse epidermis (TGHK8 mice) lead to severe epidermal phenotypes including epidermal hyperplasia associated with orthokeratotic hyperkeratosis, dysplastic hair follicles and altered expression terminal differentiation markers [75].…”
Section: Sccs and K8/k18mentioning
confidence: 97%